2017
DOI: 10.1111/maq.12366
|View full text |Cite
|
Sign up to set email alerts
|

“You Can Learn Merely by Listening to the Way a Patient Walks through the Door”: The Transmission of Sensory Medical Knowledge

Abstract: Examining the mechanisms of medical knowledge transfer, this article addresses the ways nonvisual senses are employed within medical training, asking about the role of sound, touch, and movement in transmitting knowledge of the body. Based on a 10-month ethnography in a medical massage training course for blind students, the article examines the ways sensory medical knowledge is transferred in this setting. I discuss the multisensory characteristics of medical knowledge transfer, and the dual process inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…First, we focused on learning sensory skills with technologies in medicine, a topic that to date has most extensively focused on doctors and medical students (e.g. Prentice, 2013;Rice, 2013;Hammer 2017;Maslen, 2015;Harris and van Drie, 2015). By looking at caregiver intra-actions we showed that parents also undergo sensory training in their care of their children, a training that uses similar embodied techniques and technologies, such as recordings and mimicry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we focused on learning sensory skills with technologies in medicine, a topic that to date has most extensively focused on doctors and medical students (e.g. Prentice, 2013;Rice, 2013;Hammer 2017;Maslen, 2015;Harris and van Drie, 2015). By looking at caregiver intra-actions we showed that parents also undergo sensory training in their care of their children, a training that uses similar embodied techniques and technologies, such as recordings and mimicry.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing interest in the social sciences on the sensory training of medical professionals, with studies particularly addressing how doctors and nurses learn to listen (Maslen, 2015;Harris and van Drie, 2015;Bijsterveld, 2019;Hammer, 2017;Krebs and Van Drie, 2014), touch (Kelly et al, 2019;Kuriyama, 1999;Prentice, 2013;Harris, 2016), and see (Atkinson, 1995;Saunders, 2008) in conversation with a vast body of literature on medical training in sociology and anthropology (e.g. Holmes et al, 2011;van der Geest and Finkler, 2004), and histories of medicine that deal with sensing (see Howes and Classen, 2013).…”
Section: Sensing Health and Diseasementioning
confidence: 99%
“…While Sewell addresses rules of “grammar, mathematics, law, etiquette, or carpentry,” embodied translation adds embodied knowledge to the execution of agency, with dancers distilling, transforming, and expanding a movement into new mechanisms and expressions. Dancers’ conscious actions in this process not only emphasize agency but also continue scholarly works challenging traditional theorization of bodily learning (Hammer 2017, 141) as “‘silent and practical,’ unconscious and purely mimetic” (Downey 2010, 25).…”
Section: Translation As Distilling Transferring and Expandingmentioning
confidence: 99%
“…Her analysis of each setting demonstrates tacit calibrations of ethics, affect, and embodied practice that are inseparable from-and often constitutive of-the transmission of knowledge and technical skills that medical educators openly expect trainees to acquire. Although vision plays a significant role in these training contexts, Prentice avoids privileging sight over other modes of perception such as hearing and haptics; her approach is a conscious intervention into the predominance of vision in Western intellectual traditions, intended to make space for studying the full range of sensory and bodily practices in medical education (see also Rice 2013;Hammer 2018). Along similar lines, Fountain (2014) uses the conceptual framework of rhetoric to explore relationships between material objects, discourse, and the senses in anatomy education.…”
Section: Embodying the Eyementioning
confidence: 99%